PENGARUH SELF-REGULATED LEARNING DAN INTENSITAS MEDIA SOSIAL TERHADAP PEDAGOGICAL SKILL MAHASISWA DENGAN SMARTPHONE DISTRACTION SEBAGAI VARIABEL MODERASI - Kinasih, Juitasari Putri; Hermanto, Febrika Yogie; Pahlevi, Triesninda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The advancement of digital learning requires prospective teachers to develop adaptive pedagogical skills aligned with 21st-century educational demands. At the same time, the widespread use of digital technology and social media among university students introduces challenges in the form of smartphone-related distractions that may interfere with competency development. This study examines the relationship between Self-Regulated Learning (SRL), the intensity of social media use, and students’ pedagogical skills, while also assessing the moderating role of smartphone distraction. A quantitative survey approach was employed involving 394 education students from Universitas Negeri Surabaya selected through random sampling. Data were collected using structured questionnaires and processed through moderation regression analysis, including instrument testing, classical assumption analysis, and hypothesis testing. The findings reveal that SRL contributes positively to students’ pedagogical skills. Social media use intensity is likewise positively associated with pedagogical skill improvement. In addition, smartphone distraction weakens the relationship between SRL and pedagogical skills while strengthening the influence of social media use intensity on the same outcome. These results suggest that pedagogical competence development is shaped by self-regulation capacity, patterns of social media engagement, and balanced management of digital distraction. ABSTRAK Perkembangan pembelajaran digital menuntut mahasiswa calon guru memiliki kemampuan pedagogik yang mampu menyesuaikan diri dengan kebutuhan pendidikan abad ke-21. Di sisi lain, penggunaan teknologi digital dan media sosial yang semakin tinggi juga menghadirkan tantangan berupa distraksi dari smartphone yang berpotensi menghambat pengembangan kompetensi tersebut. Kajian ini menginvestigasi keterkaitan Self-Regulated Learning (SRL) dan intensitas penggunaan media sosial dengan pedagogical skill mahasiswa, serta menguji peran smartphone distraction sebagai variabel moderasi. Pendekatan kuantitatif berbasis survei diterapkan pada 394 mahasiswa kependidikan Universitas Negeri Surabaya yang dipilih melalui teknik random sampling. Data diperoleh melalui angket terstruktur dan dianalisis menggunakan regresi moderasi melalui tahapan pengujian instrumen, asumsi klasik, dan hipotesis. Analisis menunjukkan bahwa SRL memiliki kontribusi positif terhadap keterampilan pedagogik mahasiswa. Intensitas penggunaan media sosial juga berkorelasi positif dengan peningkatan pedagogical skill. Selain itu, smartphone distraction memperlemah hubungan antara SRL dan keterampilan pedagogik, tetapi memperkuat pengaruh intensitas penggunaan media sosial terhadap keterampilan tersebut. Temuan ini mengindikasikan bahwa pengembangan kompetensi pedagogik mahasiswa tidak hanya dipengaruhi oleh kemampuan regulasi diri, tetapi juga pola pemanfaatan media sosial dan pengelolaan distraksi digital secara seimbang.